A lifelong portfolio for the teaching profession - Margherita Di Stasio; Lorella Giannandrea; Patrizia Magnoler; Elena Mosa; Maria Chiara Pettenati; Pier Cesare Rivoltella; Pier Giuseppe Rossi; Anna Tancredi (Firenze University Press, 2021)
The portfolio can be an effective device to support the professional growth of the teacher. Today there is no online portfolio with a similar rationale that can be used in the various moments of growth from initial teachers' education to in-service training. The various experiences of the use of the portfolio proceed separately, with a certain fragmentation that makes it difficult to think in terms of lifelong learning. In this contribution, we describe the joint initiative of Indire and the Catholic University of the Sacred Heart and the University of Macerata, aimed at designing a device to encourage the reflexivity of the teachers, accompanying them throughout the phases of their career. In this paper we discuss the various models of teacher portfolios in order to begin the discussion on a model that can find continuity of experimentation and then application at the national level in the various stages of the teacher's professional development.   Un portfolio lifelong per la professionalità docente Il portfolio può costituire un dispositivo efficace per supportare la crescita professionale del docente. Oggi non esiste un portfolio online con una logica simile che possa essere utilizzato nei vari momenti della crescita dalla formazione iniziale universitaria a quella in servizio. Le varie esperienze d' uso del portfolio per ora procedono separate, e ciò produce una certa frammentarietà che rende difficoltoso e artificioso ragionare in ottica di lifelong learning. Nel contributo descriviamo l'iniziativa congiunta di Indire e delle Università Cattolica del Sacro Cuore e dell'Università di Macerata, orientata a progettare un dispositivo per favorire la riflessività del docente accompagnandolo con continuità nelle fasi della propria carriera. In questo lavoro si discutono i vari modelli di portfolio docente per avviare la discussione su un modello che possa trovare continuità di sperimentazione e poi di applicazione a livello nazionale nei vari stadi dello sviluppo professionale del docente.